Pelatihan Penyusunan Laporan Keuangan Sesuai SAK-EMKM Bagi UKM di Wilayah Kelurahan Bugangan Semarang: - - Tri Rinawati; Niati, Asih; Ariefiantoro, Teguh (ASIAN PUBLISHER, 2023)
The profile of SMEs in the Bugangan subdistrict environment is on a small business scale. SME business actors have a low level of understanding of financial reports in accordance with SAK-EMKM, where during the process of running their business, the actors still mix business finances with household finances, so there is no separate recording, so the level of business profit cannot be seen. As a follow-up, the solution offered is that the Lecturer Team at the Faculty of Economics, University of Semarang will provide training in preparing simple financial reports according to SAK EMKM using Basic Accounting Equations, Profit and Loss Reports, Changes in Capital Reports, Balance Sheet Reports and Statements of Cash Flows. Community service activities are carried out using lecture, training and discussion/question and answer methods. The work procedure for service activities is carried out through several stages including the identification stage, the preparation stage, the implementation stage, the monitoring and evaluation stage, the reporting and publication stage. The community service activity program will be held on Saturday, June 8 2023. The community service activity will be held at Balai RW 07 Jl. Serayu I, Bugangan Village, East Semarang District. This activity is carried out for 1 (one) day from 11.00 to 14.00 (1 x 3 hours). Service participants were very enthusiastic in participating in training activities. Service participants felt greatly helped by the training activities.